Commitment profiles, job satisfaction and behavioral outcomes - Dello Russo, S.; Vecchione, M.; Borgogni, L. (Applied Psychology: An International Review, 2013)
Past research adopting a configural approach to organisational commitment has yielded support for differentiated profiles (i.e. different combinations of different levels of commitment components) and for their relationship with attitudinal and behavioral outcomes. The present study aimed to: (a) investigate, in an Italian privatised organisation, the emergence of commitment profiles derived from the combination of affective (AC) and continuance (CC) organisational commitment, following Sinclair and colleagues' conceptualisation (2005); and (b) examine whether these profiles differed in absenteeism, as an objective outcome, job satisfaction, and job performance. Results from cluster analysis supported the presence of four groups (Allied, Free Agents, Trapped, and Complacent). The Allied and the Complacent profiles reported higher job satisfaction. Moreover, the Complacent profile displayed the highest job performance and the Allied showed the lowest level of absenteeism; both were significantly different from the Trapped profile. Implications for theory and practice are discussed.